Potent induction of trained immunity by Saccharomyces cerevisiae β-glucans - Vuscan, Patricia; Kischkel, Brenda; Hatzioannou, Aikaterini; Markaki, Efrosyni; Sarlea, Andrei; Tintoré, Maria; Cuñé, Jordi; Verginis, Panayotis; de Lecea, Carlos; Chavakis, Triantafyllos; Joosten, Leo A.B.; Netea, Mihai G. (Frontiers in Immunology, 2024)
Candida albicans cell wall component β-glucan has been extensively studied for its ability to induce epigenetic and functional reprogramming of innate immune cells, a process termed trained immunity. We show that a high-complexity blend of two individual β-glucans from Saccharomyces cerevisiae possesses strong bioactivity, resulting in an enhanced trained innate immune response by human primary monocytes. The training required the Dectin-1/CR3, TLR4, and MMR receptors, as well as the Raf-1, Syk, and PI3K downstream signaling molecules. By activating multiple receptors and downstream signaling pathways, the components of this β-glucan preparation are able to act synergistically, causing a robust secondary response upon an unrelated challenge. In in-vivo murine models of melanoma and bladder cell carcinoma, pre-treatment of mice with the β-glucan preparation led to a significant reduction in tumor growth. These insights may aid in the development of future therapies based on -glucan structures that induce an effective trained immunity response.